2022
DOI: 10.3390/metabo13010002
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs Showed Specific Responses according to Metabolic Syndrome Components and Sex of Adults from a Population-Based Study

Abstract: microRNAs (miRNAs) regulate several metabolic pathways and are potential biomarkers for early risk prediction of metabolic syndrome (MetS). Our aim was to evaluate the levels of 21 miRNAs in plasma according to MetS components and sex in adults. We employed a cross-sectional study of 192 adults aged 20 to 59 years old from the 2015 Health Survey of São Paulo with Focus in Nutrition. Data showed reduced levels of miR-16 and miR-363 in women with MetS; however, men with one or more risk factors showed higher lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…These miRNAs have previously demonstrated dysregulated pro les in individuals with metabolic disorders such as prediabetes, T2DM, MetS, and obesity. Notably, hsa-miR-16-5p, found at reduced levels in Brazilian women with MetS [43], has also shown a positive correlation with insulin sensitivity in non-diabetic, weight-stable individuals. Furthermore, hsa-miR-17-5p, hsa-miR-21-5p and hsa-miR-320a are shown to have decreased abundance in metabolically dysregulated individuals compared to healthy counterparts [44].…”
Section: Discussionmentioning
confidence: 96%
“…These miRNAs have previously demonstrated dysregulated pro les in individuals with metabolic disorders such as prediabetes, T2DM, MetS, and obesity. Notably, hsa-miR-16-5p, found at reduced levels in Brazilian women with MetS [43], has also shown a positive correlation with insulin sensitivity in non-diabetic, weight-stable individuals. Furthermore, hsa-miR-17-5p, hsa-miR-21-5p and hsa-miR-320a are shown to have decreased abundance in metabolically dysregulated individuals compared to healthy counterparts [44].…”
Section: Discussionmentioning
confidence: 96%
“… 5 Likewise, a prospective study reported raised levels of microRNA-30a in people with prediabetes compared to normal subjects, and this rise occurred many years before the occurrence of diabetes. 25 Also, Koh et al illustrated that the expression of microRNA-30a protected adipose tissue from the harmful effects of inflammatory mediators, leading to a reduction in insulin resistance in obese mice. 26 Conversely, the suppression of microRNA-30a was found to have a protective effect on pancreatic beta cells and enhanced glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, metabolic disorders increase the risk of cardiovascular disease (CVD) and cancer 75 . In addition, it has been highlighted that miRNA expression in plasma is a potential biomarker for obesity 76,77 . However, since AT, especially the white AT (WAT), has a major role in obesity, it is important to better understand its role in extracellular crosstalk with other tissues.…”
Section: Role Of Ev‐containing Mirnas In Obesity and Metabolic Syndromementioning
confidence: 99%